Amine-functionalized radiation-grafted nylon-6 fibers: synthesis and adsorption performance for diclofenac sodium - Abd Aziz Abdullah, Sharifah Mona; Abdullah, Luqman Chuah; Md Jamil, Siti Nurul Ain; Ting, Teo Ming; Choong, Thomas Shean Yaw (Springer Science and Business Media Deutschland, 2025)
Abstract: The removal of pharmaceutical contaminants from water sources remains a critical challenge due to the limited efficiency and high cost of the current technologies. This study presents the development of innovative fibrous adsorbents synthesized through radiation-induced graft-copolymerization (RIGC) of glycidyl methacrylate (GMA) onto nylon-6 (Ny6) fibers. These GMA-grafted fibers were subsequently functionalized with 1,3-diaminopropane (DAP) and diethylenetriamine (DETA), resulting in the formation of DAP(GMA-g-Ny6) and DETA(GMA-g-Ny6) adsorbents. By optimizing the graft yield (%), amine functionality, and reaction time, the amine densities of 3.39 and 2.66 mmol/g were achieved for DAP(GMA-g-Ny6) and DETA(GMA-g-Ny6), respectively. The analytical techniques, including FTIR, XPS, SEM, BET, TGA, and XRD confirmed successful amine incorporation and characterized the structural changes. The preliminary adsorption experimental results demonstrated that the DAP and DETA functionalized fibers exhibited high adsorption capacities, with DAP(GMA-g-Ny6) achieving a maximum diclofenac sodium removal efficiency of 99%, compared to 90% for DETA(GMA-g-Ny6). The superior performance of DAP(GMA-g-Ny6) can be attributed to its high amine density (3.00 mmol/g), which provides extensive amine group coverage on the surface of the grafted fiber, thereby facilitating strong hydrogen bonding and electrostatic interactions with diclofenac sodium molecules. These findings suggest that the amine-functionalized nylon-6 fibers synthesized through RIGC offer a promising and effective solution for the removal of diclofenac sodium from water, highlighting their potential application in environmental remediation.